Adsorption of heavy metals and bisphenol A from wastewater using Spirulina sp.-based biochar as an effective adsorbent: A preliminary study - Moon, Soeun; Lee, Youn Jun; Choi, Moon Yeong; Lee, Chang Gu; Park, Seong Jik (Journal of Applied Phycology, 2023)
This study aims to investigate the adsorption efficiencies of bisphenol A (BPA) and three heavy metals (HMs), namely Cd(II), Cu(II), and Pb(II), using microalgae Spirulina sp.-derived biochar. The Spirulina biomass was subjected to heat treatment within a temperature range of 200–400 °C to produce biochar. By comparing the adsorption BPA and HMs efficiencies, it was found that the Spirulina sp.-based biochar heat-treated at 200 °C (SPBC200) was the optimal adsorbent for further investigation. The removal efficiencies of SPBC200 for BPA, Cd(II), Cu(II), and Pb(II) were 60.59 ± 0.02%, 95.21 ± 0.22%, 96.02 ± 0.10%, and 97.58 ± 0.03%, respectively. The adsorption kinetics of BPA and HMs on SPBC200 were effectively described by the pseudo-second-order model. In addition, the intra-particle diffusion model demonstrated two or three stages of the adsorption process. The adsorption isotherms were well-fitted using the Redlich-Peterson model. Moreover, by altering their initial concentrations, the simultaneous adsorption of BPA and HMs was investigated. The adsorption efficiencies of BPA, Cd(II), Cu(II), and Pb(II) by SPBC200 were found to range between 56.02 and 60.59%, 94.36 and 95.21%, 94.30 and 96.02%, and 97.58 and 99.57%, respectively. These outcomes suggest that there were no significant disparities in the adsorption efficiencies, providing evidence that the pollutants were adsorbed onto distinct sites of the adsorbent without any interference between them. Therefore, Spirulina sp.-based biochar demonstrated its potential as an effective adsorbent for the removal of BPA and HMs from wastewater. The findings of this study highlight the promising applications of this type of biochar in wastewater treatment and environmental remediation efforts.
Keywords: Binary adsorption; Biochar; Bisphenol A; Heavy metals; Microalgae